Female haircare purchase? Choices and Preferences- Study of South African Consumer - Katrodia, Ankit; asitile, ogone (AMAR (Andalas Management Review), 2025)
This study focuses on women's purchase intentions for hair care products. Purchase intentions influence the possibility of purchasing a product or service and lead to real buying behaviour and Customer’s purchase intention of haircare products depends on, among other factors: quality and value, satisfaction, price sensitivity, social influence and packaging which might directly influence behavioural intentions. The study seeks to explore different factors leading to purchase intention and provide suggestions on how the factors can be influenced to keep and generate customers. The study's main objective is to get a deeper understanding of the factors that influence the purchase intention of haircare products amongst women in the North West province and provide recommendations on how marketers can use those identified factors. The results showed that consumers are generally happy with the hair care products they use, however there is still room for improvement for product development as of respondents some responses indicated that brands respondents have still fall short of consumer expectations. Brands must deliver consistent good quality of products as results show that consumers can easily choose from other brands or stores. Consistent quality of products builds a consistent customer base. The researcher generated Primary information from the sampled females in and around the North-West province. The demand and intention to purchase hair care products is growing. Marketers should use social media platforms to engage with consumers and build a brand image as most of the consumers are young adults with social media presence.